FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN KERJA PEGAWAI BALAI KESEHATAN INDERA MASYARAKAT PROVINSI JAWA TENGAH - Sabrilla Putri Gotama; Septo Pawelas Arso; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2018)
ABSTRACTSense-Community Health Center becomes one of the attention of local governments in reducing the incidence of high sensory health problems in Central Java. Job satisfaction becomes organization need to improve the service quality. The increasing number of patient visits and the absence of additional human resources makes the high workload led by inadequate employee benefits and high absence also indicates that employee has low job satisfaction. This research type is observasional with survey method and cross sectional approach. The research instrument uses a structured questionnaire for all employees of BKIM Central Java Province, which are 57 people. The research data was processed quantitatively with univariate and bivariate method using chi square test. The univariate analysis shows that high percentage of compensation (50,9%), good working condition (57,9%), good organization policy and administration (70,2%), good co-worker (63,2%), high achievement (68,4%), the work itself (61,4%), good responsibility (63,2%), good opportunity (68.4%), and high job satisfaction (52.5%). Meanwhile, the result of bivariate analysis shows that there is a significant correlation between compensation, working condition, policy and organization administration, co-worker, supervision, achievement, job itself, developing opportunity with employees’ job satisfaction (p<0,05) while responsibility has no relationship with employees’ job satisfaction (p>0,05). The recommendations that can be used in managing employees’ job satisfaction is supervision can give feedback for the works that all employees have done.